Control of the Microhardness to Young Modulus Ratio by Mechanical Processing of a Ti-10Mo-20Nb Alloy - Gabriel,Sinara Borborema (2015)
β-metastable titanium alloys with high strength to Young’s modulus ratio have been developed by different authors aiming their use as biomaterials for hard tissue replacement. However, it is not easy to combine low elastic modulus with high mechanical strength. In this work, a β-Ti alloy (Ti-10Mo-20Nb) was produced by arc-melting, then homogenized, cold swaged and aged in order to obtain fine α-Ti precipitates in a β-Ti matrix. The microstructures were characterized by transmission electron microscopy and X-ray diffraction. Mechanical properties characterization was based on Vickers microhardness tests and Young’s modulus measurements. The cold swaged material subjected to an ageing treatment at 500 °C for 4 h showed the highest hardness/ Young’s modulus ratio, associated to very fine α phase precipitates in a β-Ti matrix.